Nebulization with Bromhexine and Gentamicin For Chronic Rhinitis Accompanied by Multiple Ectoparasite Infestations in a Domestic Cat - Luh Gede Tasya Pradnya Prastistha; Putu Ayu Sisyawati Putriningsih; I Gusti Made Krisna Erawan (Universitas Airlangga, 2026)
Background: Chronic rhinitis in cats represents a persistent inflammatory condition of the upper respiratory tract, frequently complicated by secondary bacterial infections and exacerbated by comorbidities, such as ectoparasite infestations. Protracted infections significantly diminish feline quality of life, necessitating a comprehensive therapeutic approach to address both primary etiologies and contributing factors. Purpose: Evaluation was undertaken regarding the efficacy of combination nebulization therapy utilizing bromhexine hydrochloride and gentamicin sulfate in ameliorating clinical symptoms of chronic rhinitis in a domestic cat concurrently infested with Sarcoptes scabiei and Felicola subrostratus. Case(s): Presentation of a domestic cat was made for persistent sneezing exceeding one month in duration, accompanied by bilateral mucopurulent nasal discharge, wheezing, severe pruritus, and crusted cutaneous lesions. Identification of Streptococcus sp. was achieved through cytology and culture of nasal secretions, while infestations of Sarcoptes scabiei and Felicola subrostratus were confirmed via trichogram and flea comb examination. Chronic inflammatory processes were further evidenced by hematological findings of leukocytosis and lymphocytosis. Case Management: Therapeutic intervention was executed through nebulization involving bromhexine hydrochloride as a mucolytic agent and gentamicin sulfate as a localized antibiotic. This regimen was integrated with systemic methylprednisolone for inflammation suppression, spot on selamectin for ectoparasite control, and nutritional supplementation to facilitate systemic recovery. Conclusion: Favorable clinical responses in the management of feline chronic rhinitis were demonstrated by the combination of nebulized bromhexine and gentamicin. Significant amelioration of respiratory symptoms was observed within seven days, whereas resolution of cutaneous lesions and ectoparasite infestations was evident by day 14. Effectiveness in enhancing clinical outcomes in complex cases with multifaceted comorbidities is highlighted by this integrated therapeutic approach.